STYLISTICS ANALYSIS ON LITERATURE LEARNING MATERIAL OF BAHASA INDONESIA CURRICULUM 2016 SMA-MA-SMK - Esti Ismawati; Sukasih Ratna Widayanti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
ABSTRACT This study aims to analyze literature learning material Class X SMA-MA-SMK in Curriculum Bahasa Indonesia 2016. The method is descriptive by referring to the stylistics study. The problem is how is the linguistic description of literature learning material above?. The findings can be concluded that the poet uses the single and complex sentences. It also uses the rhetorical sentence, parallelism, repetition, metaphor, and climax in poems. The chosen vocabulary by the author is the common vocabulary which they use in our daily life, however it has special meaning when it is arranged in the form of poetry. The imagination in their poems is very strong. It can be seen through visual, auditory, and tactile. Keywords: stylistics study, linguistics aspect, literature material, curriculum 2016